ANALYSIS OF EFFICIENCY AND ELASTICITY OF LABOR ALLOCATION IN MANUFACTURING INDUSTRY IN INDONESIA - Nababan, Tongam Sihol; Panjaitan, Raya; Panjaitan, Ferry; Sihombing, Eriko; Nopeline, Nancy (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
AbstractThe purpose of this study is to analyse the level of efficiency and elasticity of the large and medium manufacturing industry sector during 2012 - 2020 in the Indonesian Standard Industrial Classification (ISIC) 2-digit level (major groups 10 to 33), consisting of 24 types of manufacturing sub-industries. In this study, the Cobb-Douglas production function model with linear logarithmic was used to analyse the manufacturing efficiency index. The results showed that: (1) during the period 2012-2020, the production efficiency of the 2-digit ISIC sub-sector (24 sub-sectors) increased on average by 445% or 4. 45 times, (2) all the output elasticity values of the 2-digit ISIC subsector (24 subsectors) were less than one (EL < 1), which showed that the marginal value added of labour was lower than the average value added of labour, so that the additional allocation of labour in large and medium-sized industries tended to reduce the average value added of labour, (3) the highest efficiency index in order were ISIC 26 (computer, electronic and optical products), ISIC 17 (paper and paperboard), ISIC 18 (electrical machinery and equipment), ISIC 19 (machinery and equipment) and ISIC 20 (machinery and equipment); ISIC 17 (paper and paper products); ISIC 31 (furniture) and ISIC 29 (motor vehicles, trailers and semi-trailers).